The Tower of London Spatial Problem-Solving Task: Enhancing Clinical and Research Implementation - Berg, W. Keith; Byrd, Dana L. (Journal of clinical and experimental neuropsychology, 2002)
Since its development in 1982, The Tower of London (TOL; Shallice, 1982) spatial problem-solving task has been increasingly employed in test batteries of executive functions. This task has served as a rich source of information on preparation, planning and processing, but a number of issues remain unaddressed in the literature: (1) the problem structure, or problem space of the task, (2) the impact of modifications from the original, Shallice TOL, and (3) the variety of performance measures that can be derived from the TOL. We present here an overview of these issues in the hope that it may lead to a more effective and reasoned use of the TOL task by clinical and nonclinical investigators, alike.